Analiza odbiorców przedsiębiorstwa przetwórstwa mleczarskiego - Grzybowska-Brzezińska, Mariola (Analysis of Receivers of Dairy Processing Company, 2005)
District Dairy uses many distributions channels because it is focused on providing a wide range of products and tends to reach as many customers as it is possible.Dairy products are every day products which are bought by many people and that is why they are quite cheap. They must be used by intensive distribution. Distribution system would help with location of products at certain quantity.Reaching many dislocationed consumers has the main impact on sale. Consumers tend to keep looking for a chosen trademark and when they cannot find it, they will buy a substitute.The survey has showed that foreign channel has an important influence in a process of dairy products' distribution. There is one or two distributors in this channel. To provide a product on the market the company uses short and wide channels of distribution. This process leads to making channels longer because of using warehouses as distributors.The stability of distribution system is very important for the company. The indicator of this stability, which at the same time defines distributors, is a structure of constant customers. A constant customer buys products for the period of the survey. There also has been a survey in receivers structure. The company should pay more attention not to lose strategic customers. Their loss should be made up with getting new clients with the similar power of getting goods.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 310-316